DESIGNING COMPANY PERFORMANCE MEASUREMENT SYSTEM USING BALANCE SCORECARD APPROACH - Cecep Mukti Soleh; Idqan Fahmi; Imam Teguh Saptono (School of Business, IPB University (SB-IPB), 2015)
This research aimed to design how to measure company performance by using balance scorecard approach in coal transportation services industry. Depth interview was used to obtain qualitative data determination of strategic objectives, key performance indicators, strategic initiatives, and in charge units for each balanced scorecard perspectives while the quantitative data were obtained from weighting through questionnaires and analyzed using paired comparison to get a perspective what mostly affected the performance of the company. To measure the achievement of corporate performance, each KPI used (1) the scoring system with the methods that higher is better, lower is better and precise is better; (2) traffic light system with the help of green, yellow, red for identification of target achievement. This research result shows that in the balance scorecard perspective, the most influences on the overall performance of the company include the customer's perspective (31%), financial perspective (29%), internal business processes (21%), learning, and growth 19%). Keywords: balance scorecard, paired comparison, coal transportation serviceABSTRAKPenelitian ini bertujuan untuk merancang pengukuran kinerja perusahaan dengan menggunakan pendekatan balance scorecard di industri jasa pengangkutan batu bara. Data kualitatif diperoleh melalui indepth interview digunakan untuk menentukan sasaran strategik, indikator kinerja utama, inisiatif strategi dan penanggungjawab setiap divisi setiap perspektif balance scorecard, sedangkan data kuantitatif digunakan untuk pembobotan melalui kuesioner dan dianalisis dengan menggunakan metode paired comparisson untuk mendapatkan perspektif yang paling berpengaruh terhadap kinerja perusahaan. Ukuran pencapaian kinerja perusahaan dari setiap KPI menggunakan; (1) scoring system dengan bantuan metode higher is better, lower is better dan precise is better;(2) traffic light system dengan menggunakan bantuan warna hijau, kuning, merah untuk identifikasi pencapaian target. Penelitian ini menyimpulkan bahwa perspektif yang paling berpengaruh terhadap kinerja perusahaan adalah perspektif pelanggan (31%), kemudian diikuti oleh perspektif keuangan (29%), proses internal bisnis (21%), dan pertumbuhan dan pembelajaran (19%).Kata kunci: balance scorecard, paired comparison, jasa pengangkutan batu bara